Aquatic plants in ecotechnologies: perspectives for phytoremediation of iron and manganese (Research, Society and Development, 2021)
Phytoremediation consists of using plants to mitigate polluted environments, both terrestrial and aquatic. Although this ecotechnology has grown considerably in recent decades, the expansion of its application still faces the challenge to select plant species with such potential. In this work, two species of aquatic macrophytes, Spirodela polyrhiza and Ricciocarpus natans, were studied in laboratory experiments to evaluate its performance in removing manganese (Mn) and iron (Fe) in solution. Plants of S. polyrhiza were tested for both metals and subjected to concentrations of 10, 15, 20, 25 and 30 mg/L of Mn and Fe. While plants of R. natans were subjected to concentrations of 1, 2, 6 and 18 mg/L of Fe. The results showed that plants of S. polyrizha were able to remove 34% of Mn and up to 80% of Fe added in solution. However, the reduction in biomass and chlorophyll content was detected in these plants. The R. natans plants removed up to 50% of Fe in concentrations of 2, 6 and 18 mg/L and did not show decrease of biomass and chlorophyll in any of the tested concentrations, which show a promising result for the phytoremediation of Fe. Studies in field experiments are necessary to consider the environmental variants involved in the remediation process. However, the findings presented here bring, in the light of science, significant contributions to the phytoremediation knowledge of S. polyrizha and R. natans, aquatic species widely distributed in Brazilian water bodies.